Comparison of nab-paclitaxel plus gemcitabine in elderly versus younger patients with metastatic pancreatic cancer: Analysis of a multicentre, prospective, non-interventional study. (January 2021) - Prager, Gerald W.; Oehler, Leopold; Gerger, Armin; Mlineritsch, Brigitte; Andel, Johannes; Petzer, Andreas; Wilthoner, Klaus; Sliwa, Thamer; Pichler, Petra; Winder, Thomas; Heibl, Sonja; Gruenberger, Birgit; et al.
Abstract: Background: Pancreatic cancer (PC) ranks among the deadliest malignancies worldwide. In the MPACT study, first-line nab-paclitaxel plus gemcitabine (nab-P/G) demonstrated activity (median overall survival [OS], 8.7 months) and tolerability in patients with metastatic PC (mPC). However, the clinical evidence of nab-P/G in the elderly (>70 years), who account for the majority of patients with mPC, is limited. This is the first prospective, multicentre, non-interventional study evaluating the tolerability and effectiveness of nab-P/G in younger (≤70 years) versus elderly (>70 years) patients with mPC in the daily clinical routine. Methods: Eligible patients with mPC were treated with nab-P/G and observed until disease progression or unacceptable toxicity. The primary objectives were safety and tolerability of nab-P/G, and the secondary objectives were efficacy and real-life dosing. Results: A total of 317 patients with mPC (median age, 70 years) were recruited, of which 299, aged ≤70 (n = 162) and >70 (n = 137) years, were eligible for analysis. Baseline characteristics and the safety profile were comparable between the groups. However, fatigue (22.8% versus 13.0%) and decreased appetite (8.8% versus 1.2%) were more frequent in elderly patients. Younger versus elderly patients equally benefited in terms of objective response rate (36% versus 48%), median progression-free survival (5.6 versus 5.5 months; hazard ratio [HR] = 1.03; p = 0.81) and OS (10.6 versus 10.2 months; HR = 0.89; p = 0.4). In addition, the median treatment duration (5 versus 4 cycles), relative dose intensity (70% versus 74%) or reasons for treatment discontinuation were similar. Most patients (56.2% versus 47.4%) benefited from a second-line therapy. Conclusion: This prospective real-world analysis confirms the feasibility and tolerability of nab-P/G treatment and reveals OS data similar for younger patients and elderly patients aged >70 years. ClinicalTrials.gov registration: NCT02555813. Austrian NIS registry: NIS005071. Highlights: This is a prospective non-interventional study evaluating nab-paclitaxel and gemcitabine in metastatic pancreatic cancer (mPC). The study includes a large cohort of elderly (>70 years) patients with mPC. Elderly patients show a manageable safety profile. Efficacy and overall survival of elderly patients is comparable with those of younger patients.